A century after introduction: variability in Cepaea hortensis (Müller, 1774) in Sibiu, central Romania. (28th January 2019) - Gheoca, Voichița; Benedek, Ana Maria; Cameron, Robert A D; Stroia, Radu Camil
Abstract: The polymorphic land snail Cepaea hortensis was introduced to the city of Sibiu, central Romania, in the first decade of the 20th century and has spread widely across the city. A total of 97 locations were examined in 2017 across the city to determine the habitat preferences and variation in shell size, shape, colour and banding polymorphism of C. hortensis, and to relate these to the same features in the likely source population from Mannheim, Germany, and the first established population in Sibiu. We found that C. hortensis was largely restricted to sites with some woody vegetation cover and showed a marked preference for abandoned and overgrown private gardens. Mean adult shell size in present-day populations was almost always smaller than in both the presumed population of origin from Germany and the first recorded population from Sibiu. Populations showed a wide range of variation in frequencies of shell colours and banding morphs. This variation was not related to habitat or cover, and there was no evident geographical structure in the patterns. Comparisons with a smaller-scale sampling in 2004/5 showed that some populations had gone extinct, some remained stable and in some morph frequencies had changed drastically, but in no consistent direction. These results are similar to those obtained for the related species C. nemoralis in comparable circumstances, but differ from those obtained from regions where C. hortensis is long established and where habitats have been stable. The patterns we observed most likely reflect the effect of passive dispersal by humans, genetic drift and founder effects.